Fracture analysis on thin rotating disc with radial cracks - Lee, Jun Ming (Nanyang Technological University, 2023)
Fracture analysis of thin rotating discs can be carried out through numerical methods like Finite Element Analysis (FEA) or Boundary Element Method (BEM). These methods aim to analyze the stress concentration and intensity in the disc under different loading conditions, such as radial tension and rotation. Thin rotating discs have typically been found in aircraft engine compressors and turbines. Non-centralized holes in the disc can cause stress concentration and intensity due to discontinuity in the material. To understand the impact of these holes on the stress distribution in the disc, it is essential to analyze the Normalized Stress Concentration (Kt) and Normalized Stress Intensity (K0) values associated with these holes. Geometrical parameters are to be varied in studying how these parameters affect the Kt and K0 values of the disc under different loading conditions. Results from the stress concentration analysis reveal that the maximum principal stress is in the 180° region of the non-centralized holes for various parameters, indicating significant stress concentration at this point when undergoing rotation. In investigation of the stress intensity factor, crack lengths are varied. This investigation reveals that both the stress intensity factor and stress concentration factor decrease as the number of non-centralized holes increases, giving a downward trend. This decrease suggests with the addition of more holes, stress concentration and intensity in the disc could be potentially reduced. In conclusion, numerical methods like FEA or BEM can be used to perform fracture analysis of thin rotating discs. They can also be used to examine the effects of non-centralized holes on disc stress distribution. By understanding the Kt and K0 values, engineers can design discs that withstand high-speed rotation and other loading conditions, improving aircraft engine safety and reliability